Empirical Evidence on Cruising for Parking - Jos van Ommeren; Derk Wentink; Piet Rietveld (Tinbergen Institute, 2010)
The literature on car cruising is dominated by theory. This is the first article thatexamines cruising for parking using a nation-wide random sample of car trips. We excludeemployer-provided and residential parking. We demonstrate that cruising time is, on average, 36seconds per car trip. Car drivers appear to choose their cruising time in line with economictheory: cruising time increases with travel duration as well as with parking duration, but fallswith income. We also find that cruising is more common with shopping and recreation than forwork-related activities. Cruising has a distinctive pattern over the day with a peak in themorning, so the order of arrival is essential to parking.
Keywords: R41; 330; Cruising for parking; Ruhender Verkehr; Zeitökonomie